Herschel-ATLAS/GAMA: How does the far-IR luminosity function depend on galaxy group properties?. Issue 3 (18th June 2014) - Guo, Qi; Lacey, Cedric; Norberg, Peder; Cole, Shaun; Baugh, Carlton; Frenk, Carlos; Cooray, Asantha; Dye, Simon; Bourne, N.; Dunne, L.; Eales, S.; Ivison, R. J.; et al.
Abstract : We use the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) Phase I data to study the conditional luminosity function of far-IR (250 μm) selected galaxies in optically selected galaxy groups from the Galaxy And Mass Assembly (GAMA) spectroscopic survey, as well as environmental effects on the far-IR-to-optical colour. We applied two methods, which gave consistent results for the far-IR conditional luminosity functions. The direct matching method matches H-ATLAS sources to GAMA/SDSS (Sloan Digital Sky Survey) galaxies, then links the optical counterparts to GAMA groups. The stacking method counts the number of far-IR sources within the projected radii of GAMA groups, subtracting the local background. We investigated the dependence of the far-IR (250 μm) luminosity function on group mass in the range 10 12  <  M h  < 10 14   h −1  M⊙ and on redshift in the range 0 <  z  < 0.4, using a sample of 3000 groups containing H-ATLAS sources with GAMA redshifts over an area of 126 deg 2 . We find that the characteristic 250 μm luminosity, L *(250), increases with group mass up to M h  ∼ 10 13   h −1  M⊙, but is roughly constant above this, while it increases with redshift at high group masses, but less so at low masses. We also find that the group far-IR luminosity-to-mass ratio L (250)/ M h increases with redshift and is higher in low-mass groups. We estimate that around 70 per cent of the 250 μm luminosity density in the local Universe is contributed by groups with M h  > 10 12   h −1  M⊙ . We also find that the far-IR-to-optical colours of H-ATLAS galaxies are independent of group mass over the range 10 12  <  M h  < 10 14   h −1  M⊙ in the local Universe. We also compare our observational results with recent semi-analytical models, and find that none of these galaxy formation models can reproduce the conditional far-IR luminosity functions of galaxy groups.